Bimodal transparent alumina ceramics prepared with micro/nano-particles under high pressure. (September 2016) - Liu, Fangming; He, Duanwei; Wang, Qiang; Ding, Wei; Liu, Jin; Liu, Yinjuan
Abstract: Alumina nano-powder was used as the cement in bonding coarse spherical particles to fabricate transparent alumina ceramics under high pressure and modest temperature. Observations on the microstructure, density and microhardness of Al2 O3 specimens prepared at 500–1200 °C under 5.0 GPa provided significant effects of additive nano-particles on the sintering of samples. The high pressure initiated plastic deformation of spherical particles, rearranged nano-particles filling the clearance among spherical particles and bonding each other to densify the products. The additive particles also contribute to grain boundary strengthening to obtain samples with enhanced transparency and microhardness. Graphical abstract: